2010
DOI: 10.3390/sym2020934
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Properties of Amino Acids: A Density Functional Theory Study

Abstract: Amino acids are involved in many scientific theories elucidating possible origins of life on Earth. One of the challenges when discussing the evolutionary origin of biopolymers such as proteins and oligonucleotides in living organisms is the phenomenon that these polymers implement monomers of exclusively one handedness, a feature called biomolecular homochirality. Many attempts have been made to understand this process of racemic symmetry breaking. Assuming an extraterrestrial origin of the molecular building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…What came as a surprise from the studies of condensed amino acid CD spectra is that the α‐methylated amino acids, isovaline and α‐methyl valine, which showed the highest ee values of left‐handed enantiomers in meteorites, gave CD signals of the opposite sign compared to the family of α‐H amino acids (Figure ). The higher steric hindrance due to the methyl group in the α‐position is assumed to provide dramatic changes in the preferred realized amino acid conformation and its molecular orbitals, probably leading to reversal of the CD band. It was further shown that the molecular environment of amino acids has a great impact on the CD structure; it causes a significant difference in the peak shape and sometimes leads to inversion of the n→π* band by passing from the liquid to an amorphous state …”
Section: Chiroptical Response and Absolute Asymmetric Formation Of Ammentioning
confidence: 99%
“…What came as a surprise from the studies of condensed amino acid CD spectra is that the α‐methylated amino acids, isovaline and α‐methyl valine, which showed the highest ee values of left‐handed enantiomers in meteorites, gave CD signals of the opposite sign compared to the family of α‐H amino acids (Figure ). The higher steric hindrance due to the methyl group in the α‐position is assumed to provide dramatic changes in the preferred realized amino acid conformation and its molecular orbitals, probably leading to reversal of the CD band. It was further shown that the molecular environment of amino acids has a great impact on the CD structure; it causes a significant difference in the peak shape and sometimes leads to inversion of the n→π* band by passing from the liquid to an amorphous state …”
Section: Chiroptical Response and Absolute Asymmetric Formation Of Ammentioning
confidence: 99%
“…Boltzmann population weighted theoretical CD curves recently confirmed opposite signs for non-ionic l-valine and l-isovaline in the gas phase between 130 and 180 nm. [16] Previous experimental work using a commercial CD photospectrometer indicated the potentially opposite circular dichroic sign of isovaline with valid data down to 180 nm where the absorption became saturated. [17] The aforementioned theoretical spectra of neutral molecules in the gas phase are not directly transferable to interstellar chemistry or our experiments.…”
Section: Dedicated To Professor Henri B Kagan On the Occasion Of Hismentioning
confidence: 99%
“…The free energies for each stereoisomer of PC oligomers were obtained by the addition of thermal corrections derived from frequency calculations to the energies of each fully optimized structure in the gas phase and single‐point energies in octanol and water (M05‐2X/6‐31G**, 298 K). [ 32 ] Then, these free energies were used to obtain populations of conformers according to the Boltzmann distribution law represented in the following equation: NiN=enormalGi/kTeGi/italickT=eG/RTenormalG/italicRT0.25em where the natural logarithm of the ratio of the number of molecules in different energy levels at ground state is proportional to the negative of their energy separation. [ 33 ] The variable N i corresponds to a fraction of molecules at a determined conformation at ground state.…”
Section: Methodsmentioning
confidence: 99%